Political Mobilisation and Discourse Networks: A New Youth and the Breakdown of the Soviet Union. Issue 10 (26th November 2017) - Krawatzek, Félix
Abstract: The disintegrating discourse about youth during the perestroika period conveyed the fading legitimacy of the Soviet political order. During that era (1985–1991), media reports about young people's discontent and political disillusionment questioned the very legitimacy of the Soviet system. Youth took to the streets early, contributing to the conditions needed to conceive of a possible failure of the USSR. This research uses a recent methodological development in text analysis—discourse network analysis—which allows for an analysis of the shifting paradigms of speaking about youth. I draw on a sample of newspaper articles to capture the variation of the heterogeneous Soviet discourse.